ANALISA VARIABEL FINANCING TO ASET RATIO, RATE OF RETURN TO FINANCING RATIO DAN FINANCING TO DEPOSIT RATIO TERHADAP KEPUTUSAN PEMBIAYAAN MURABAHAH PADA PT. BANK ACEH SYARIAH - Cut Delsie Hasrina; Azlim Azlim; Yusri Yusri (Politeknik Negeri Lhokseumawe, 2019)
PT. Bank Syariah Aceh that converted into sharia bank since 19 September 2016 is the largest sharia bank in Aceh Province. The purpose of this research was to determine the effect of financing to asset ratio (FAR), rate of return on financing ratio (RFR) and financing to deposit ratio (FDR) both simultaneously and partially on murabahah financing decisions at PT. Bank Aceh Syariah. The object of this research was FAR, RFR and FDR both simultaneously and partially on murabahah financing decisions. The period of observation started from September 2016 to June 2018. The data for this research are secondary data and data analysis using multiple linear regression. This research is a census research so that significant testing is not carried out on the value of the regression coefficient obtained. The results showed that simultaneous testing on financing to asset ratio (FAR), rate of return on financing ratio (RFR) and financing to deposit ratio (FDR) had an effect on murabahah financing decisions. Furthermore, partially testing on all factors of financing to asset ratio (FAR), rate of return on financing ratio (RFR) and financing to deposit ratio (FDR) affected on the murabahah financing decision. Keywords: financing to asset ratio, rate of return on financing ratio, financing to deposit ratio, murabahah financing